The Fetishized Identity Economy: Persona Capital, Staged Class, Platform Capitalism on Short-Video Platforms - Chunfeng Lin (Social Media + Society, 2025)
The rise of short-video platforms has transformed identity into a hyper-commodified asset, merging performative self-presentation with algorithmic governance. This article introduces the fetishized identity economy (FIE), a theoretical framework that reinterprets Marxian commodity fetishism, Bourdieusian symbolic capital, and Baudrillardian hyperreality to analyze how digital personas are constructed, staged, and monetized. The FIE framework centers on three interrelated concepts: persona capital (algorithmically optimized self-performance), staged class (the commodification of social status as symbolic spectacle), and platform capitalism (the cultural and ideological shaping of profitable identity performances). Through a case study of Chinese influencer Sister Yu, the article illustrates how identity under the FIE is engineered rather than expressed, shaped by state-platform synergies that reward particular narratives of gender, labor, and class. By doing so, this study critiques the neoliberal assumptions embedded in Western influencer discourse and offers an alternative lens to understand the complex interplay of identity, governance, and platform logics. The research contributes to ongoing debates on platform labor, attention economies, and the global contours of influencer culture.